Gertrude Stein. - Hoffman, Frederick J. (University of Minnesota pamphlets on American writers, 1961)
Gertrude Stein - American Writers 10 was first published in 1961. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.